The Effect of Deep Breathing Relaxation Intervention to Reduce Pain Intensity in Gastritis Patients: A Scoping Review - Rani Anggraeni; Siti Umaemah; Nabila Isty Dwi Nur Anjani; Shinta Arini Ayu; Siti Yulianti; Rhifa Sasqi Nurazijah; Resti Oktaviani; Novia Febriyanti (Jurnal Kesehatan, 2025)
Introduction: An inflammatory condition affecting the gastric mucosa is called gastritis. This inflammation can cause swelling of the gastric mucosa to the detachment of the superficial mucosal epithelium which is the most important cause of disorders in the digestive system. Pain is an unpleasant sensory and emotional experience due to actual and potential tissue damage. Deep breathing relaxation is intended to reduce muscle tension, and anxiety to prevent increased pain stimuli, as one method of pain management. Method: Selected articles from the literature are reviewed and used in this study. Results: This scoping review shows that from 7 articles that meet the inclusion and 5 supporting articles that have been reviewed, deep breathing relaxation therapy has an effect on reducing the pain scale. Conclusion: Based on several explanations that have been put forward, that providing breathing relaxation therapy used for the process of pain management is very helpful in relieving the pain experienced by patients, therefore facilitating the healing process and this technique is very easy to do independently by patients. Conclusion: Deep breathing relaxation techniques are effective in reducing pain intensity in gastritis patients, so they can be included in nursing interventions in the nursing diagnosis of pain comfort disorders.